A taxonomic revision of the Meranoplus F. Smith of Madagascar (Hymenoptera: Formicidae: Myrmicinae) with keys to species and diagnosis of the males - Boudinot, Brendon E.; Fisher, Brian L. (Zootaxa, 2013)
The species-level taxonomy of the ant genus Meranoplus F. Smith from Madagascar is revised. Two new species, M. cryptomys sp. n. and sylvarius sp. n. are described from workers and queens; M. mayri Forel, 1910, and M. radamae Forel, 1891, are redescribed, and queens and males for these two species are described for the first time. The first diagnosis of Meranoplus males for any biogeographic region is provided based on Malagasy species. Illustrated keys to all known Malagasy castes and species are presented. Diagnoses are given for two species groups: the M. mayri group and the M. nanus group. The diagnosis of the M. nanus species group from Bolton (1981) is thereby expanded with six new characters. Two species are known from the M. mayri species group and seven described species are known for the M. nanus species group, including the two new species described herein. The mouthparts, genitalia, and all castes, where known, of Malagasy Meranoplus are illustrated.